Chinatown in Madura as urban heritage branding: Potential and challenges - Rakhmawati, Yuliana; Silviana, Rizka Dian; Wijayani, Qoniah Nur (Universitas Padjadjaran, 2024)
Background: Chinatowns have become popular tourist destinations in various prominent locations worldwide. Similarly, several Chinatowns around the cities in Indonesia, including Bangkalan in Madura, can potentially be developed as an attractive tourist destination. Purpose: This study explored the potential of Chinatown to grow as a city branding tourism in Bangkalan. Methods: It employed a qualitative descriptive method to understand the potential and obstacles to developing Chinatown in Bangkalan, Madura. Data was collected using open-ended interviews, semi-participatory observation, and related documentation. Informants comprised local Chinatown residents, cultural observers, tourism agents, and local government authorities or regulators. Spradley’s taxonomic analysis was used to map findings into thematic categories. Triangulation and observation persistence were used as techniques to ensure the data validity. Results: Based on the destination branding theory and SWOT analysis, Chinatown in Bangkalan has strength in accessibility, supporting facilities, heritage buildings, and Madurese Chinese culture. Meanwhile, weaknesses were found in regulation and coordination among the parties involved. Conclusion: Chinatown in Bangkalan can potentially be developed as an urban heritage branding by harnessing accessibility, supporting facilities, and heritage buildings while simultaneously mitigating the barriers. Implications: The research results can be a guide for policy brief formulation and insights for related stakeholders. Subsequent research can further explore the perceptions of Chinatown tourism enthusiasts from a diverse demographic perspective.